Combined transcriptome and metabolome analyses reveal the potential mechanism for the inhibition of Penicillium digitatum by X33 antimicrobial oligopeptide - Shuhua Lin (SpringerOpen, 2021)
Abstract Penicillium digitatum is the primary spoilage fungus that causes green mold during postharvest in citrus. To reduce economic losses, developing more efficient and less toxic natural antimicrobial agents is urgently required. We previously found that the X33 antimicrobial oligopeptide (X33 AMOP), produced by Streptomyces lavendulae X33, exhibited a sterilization effect on P. digitatum. In this study, the effects, and physiological mechanisms of X33 AMOP as an inhibitor of P. digitatum were investigated. The transcriptional and metabolome profiling of P. digitatum exposed to X33 AMOP revealed 3648 genes and 190 metabolites that were prominently changed. The omics analyses suggested that X33 AMOP mainly inhibited P. digitatum growth by affecting cell integrity, genetic information delivery, oxidative stress tolerance, and energy metabolism. These findings provide helpful information regarding the antimicrobial mechanism of X33 AMOP against P. digitatum at the molecular level and indicate that X33 AMOP is a potential candidate to control P. digitatum. Graphical Abstract